2021
DOI: 10.3389/fimmu.2021.684014
|View full text |Cite
|
Sign up to set email alerts
|

Potent SARS-CoV-2-Specific T Cell Immunity and Low Anaphylatoxin Levels Correlate With Mild Disease Progression in COVID-19 Patients

Abstract: T cells play a fundamental role in the early control and clearance of many viral infections of the respiratory system. In SARS-CoV-2-infected individuals, lymphopenia with drastically reduced CD4+ and CD8+ T cells correlates with Coronavirus disease 2019 (COVID-19)-associated disease severity and mortality. In this study, we characterized cellular and humoral immune responses induced in patients with mild, severe and critical COVID-19. Peripheral blood mononuclear cells of 37 patients with mild, severe and cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 50 publications
(62 reference statements)
2
44
0
Order By: Relevance
“…Previous studies have shown that critical COVID-19 patients develop higher titers of SARS-CoV-2 antibodies than those with milder disease, suggesting that antibody response alone is insufficient to avoid severe disease [10]. Our results support nonetheless that critical COVID-19 patients would need to mount a robust anti-S antibody response to survive.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have shown that critical COVID-19 patients develop higher titers of SARS-CoV-2 antibodies than those with milder disease, suggesting that antibody response alone is insufficient to avoid severe disease [10]. Our results support nonetheless that critical COVID-19 patients would need to mount a robust anti-S antibody response to survive.…”
Section: Discussionsupporting
confidence: 79%
“…CV2CoV induced both antigen-specific memory B cell responses and T cell responses. While the correlates of protection in this study were binding and neutralizing antibodies 34,35 , it is likely that CD8 + T cells contribute to viral clearance in tissues 36,37 . We previously reported that depletion of CD8 + T cells partially abrogated protective efficacy against SARS-CoV-2 re-challenge in convalescent macaques 22 .…”
Section: Discussionmentioning
confidence: 61%
“…It is also well established that intranasal vaccination promotes the induction of virus‐specific T lymphocytes in the lungs [ 7 , 8 ]. Clinical studies have shown a good correlation between disease resolution and T lymphocyte response [ 22 , 23 ]. We, therefore, compared CD8 T‐cell response in mice upon intranasal or intramuscular immunization with ChAdOx1‐S (Fig.…”
Section: Resultsmentioning
confidence: 99%